Serially Concatenated Low-density Parity Check Codes as Compatible Pairs - Ali Jassim, Amjad; A. Hadi., Wael; Ismael Ibrahim Al-Firas, Muhanned (International Journal of Engineering and Technology, 2018)
Low-density parity checks (LDPC) codes are considered good performance error correction codes. However, decoder complexity increases with increasing code length. In this study, we introduce short-length serially concatenated LDPC codes. The proposed technique uses pairs of compatible LDPC codes that act as outer and inner serially concatenated codes. In this code pair, the inner code takes input that is the same length as the outer LDPC encoder output. This study examined two cases of LDPC codes as compatible pairs with low numbers of iterations and compared bit error rate (BER) performance to a standalone LDPC code with an additive white Gaussian noise channel. We also considered the quadrature phase shift keying QPSK, 16-quadrature amplitude modulation (QAM), and 64-QAM system modulation schemes. Simulation results demonstrate that the proposed system has good BER performance compared to a standalone LDPC code, the results summarized in table and performance curves.Â Â Â